Synthesis of Some Distinct Curcumin-Based Pyrano [2,3-D] Pyrimidines with Barbituric Acid, Cinnamaldehyde, and Benzaldehyde - Kam Natania; Riviana Susanto; Antonius Herry Cahyana (Reaktor, 2023)
Curcumin is a powerful radical oxygen scavenger. The modification of of curcumin’s α, β-unsaturated 1,3-diketone moiety can be carried out to improve its physicochemical stability and functionality. This research aimed to conduct a modification of curcumin structure and to study the antioxidant activity of the modified curcumin-based compound. The modified curcumin made from a combination of benzaldehyde and cinnamaldehyde, using barbituric acid and combination of citric acid as catalyst and ethanol as solvent. The combination of ethanol solvent and 20 mmol% citric acid catalyst produce the highest yield of curcumin product which has a yield of 99.3581±0.2873% and was chosen as the best combination for the next modification using different β-diketone compounds. In the following stage, the mixture was reacted with either benzaldehyde or cinnamaldehyde. Yield, TLC, and antioxidant activity parameters were assessed for all modified products and were accompanied by their characterization using UV-Vis spectrophotometry. This study showed that curcumin cinnamaldehyde had a yield of 47.4831±2.7032%, a maximum wavelength of 416 nm, and antioxidant activity of IC50 18.2130±2.8766 mg/L with a molecular mass of 594 m/z. Keywords: antioxidant activity, benzaldehyde, cinnamaldehyde, curcumin, dimedone, modification